Layanan Informasi pada Situs Web DataGo Berdasarkan Indikator Manfaat Sistem Informasi di Kota Magelang - Muhammad Hazmi Fuadi; Siti Isti’adatul Munawaroh; Sharma Rizky Eviana; Faid Adhitya; Joko Tri Nugraha (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
The DataGo portal is a digital-based public information service developed by the Magelang City Government to improve transparency, accountability, and ease of data access for the public. This study aims to describe the benefits of the information system perceived by users and analyze their perceptions of ease of access, information quality, data search efficiency, and service usability on the DataGo portal. The research method uses a descriptive quantitative approach with a five-point Likert-scale questionnaire instrument distributed to 100 active respondents from September to October 2025, and the data is processed using descriptive statistical analysis assisted by SPSS. The results show that the majority of respondents gave a positive assessment of the benefits of the DataGo portal information system, especially in aspects of ease of access, accuracy and relevance of information, and data search efficiency which are considered capable of increasing productivity and supporting the needs of data-based decision-making. These findings indicate that the DataGo portal has functioned effectively as a means of providing public information, although it is necessary to improve the quality of the interface, regular data updates, and the development of interactive features to maximize the user experience.